Studies On The Utility Of Ndv- Specific Antibodies Inbroilerswith Maternally Derived Antibodies By A Lasota Strain Booster Vaccination Program - Sravani G; P.I.Ganesan (The Indian Veterinary Journal, 2024)
Studies on the estimation of the broilers vaccinated on 7th day and 28th day of the age with lento genic strains of Newcastle Disease in Ven-cobb broiler chicks were carried out in the broiler unit of Livestock farm complex, Apollo College of Veterinary Medicine, Jaipur, after estimating the maternally derived antibodies (MDA)on zero day of the age of the broiler chicks. The MDA hemagglutination inhibition (H.I titre) values ranged between log 22-24.Thesera samples were assessed for their hemagglutination inhibition values on 23rd, 32nd, 38th and 46th days of age of the broiler chicks. The hemagglutination inhibitiontitre values were log 24-26 on 16th day,log 25–log 27on day’s 23rd and 32nd respectively. The hemagglutination inhibition titre values on 38th and 46th days of age of the chicks were log26&log 25 respectively. The study revealed the immune status of the broilers with Newcastle lento genicsingle booster vaccination program under farm conditions with maternal antibody statusof H.I titre valueslog 22-log 24.